Pelestarian Budaya melalui Pelatihan Batik Cap Lokal Khas Desa Ngadirejo Kecamatan Jabung - Hilmi, Danial; Ilham Hanif Rahman; Muhammad Fairus Al-Hakim (Madani: Jurnal Pengabdian Ilmiah, 2024)
This study examines the implementation of a cultural preservation initiative through local stamped batik training in Ngadirejo village. Using the Asset Based Community Development (ABCD) methodology, the research focuses on leveraging community assets, particularly the village's strategic location on Mount Bromo's slopes and its agricultural commodities, notably coffee and durian plantations. The training program engaged 30 female participants and was conducted through multiple stages, including theoretical foundations and hands-on workshops led by an expert facilitator. The intervention strategy encompassed several phases: basic knowledge dissemination, wax heating techniques, stamping processes, motif enhancement, dyeing procedures, and appropriate drying methods. The training incorporated distinctive local motifs featuring Ngadirejo's coffee beans, durian fruits, and Mount Bromo landscape, creating a unique identity for the village's batik products. Observational data and interviews revealed high participant engagement and enthusiasm throughout the program, particularly during practical simulations. The initiative resulted in the successful acquisition of batik-making technical skills and led to plans for establishing a local batik production enterprise. Additionally, the program fostered community commitment to sustain batik production as both a cultural preservation effort and an economic development opportunity, demonstrating the effective integration of traditional craftsmanship with local cultural.